Trust and the public vaccine debate in Finland before and during the COVID-19 pandemic - Kuusipalo, Aapo (Routledge, 2025)
This chapter analyses Finnish vaccine-related discourses in both mainstream media and alternative channels, with particular focus on discourses relating to hesitant and critical views and the concept of trust. Conceptual delineations between trust and confidence, as well as mistrust and distrust, are utilised to analyse the methods of building trust and orientations of non-trusting positionings. The analysis offers insight into the interplay between a vaccine-critical discourse originating amongst medical and scientific professionals and a mainstream discourse rooted in a national context characterised by high generalised trust and high vaccine uptake.
Confidence was identified as the prevalent mode of trust-building in both mainstream and alternative channels, while trust-based argumentation also played a significant role, especially in the alternative discourse. Mistrust was generally more descriptive regarding the orientation of the alternative discourse, although a temporal shift towards a more distrusting focus was also observed. The marginalising reporting practices of the mainstream discourse reflected an inherent untrustworthiness linked to vaccine-critical actors and gave little possibility for trust-constructive dialogue in Finnish public discussion.
Vaccine Hesitancy in the Nordic Countries : Trust and Distrust During the COVID-19 Pandemic